Chloroquine, an Anti-Malaria Drug as Effective Prevention for Hantavirus Infections - Vergote, Valentijn; Laenen, Lies; Mols, Raf; Augustijns, Patrick; Van Ranst, Marc; Maes, Piet (Frontiers in Cellular and Infection Microbiology, 2021)
We investigated whether chloroquine, could prevent hantavirus infection in vitro and in vivo, using the Hantaan virus newborn C57BL/6 mice model and the Syrian hamster model for Andes virus. In vitro antiviral experiments were performed using Vero E6 cells and Old World and New World hantavirus species. Hantavirus genomes were detected using quantitative RT-PCR. For all hantavirus species tested, results indicate that the IC50 of chloroquine (mean 10.2 ± 1.43 μM) was significantly lower than the CC50 (mean 260 ± 2.52 μM), yielding an overall selectivity index of 25.5. We also investigated the potential of chloroquine to prevent death in newborn mice after Hantaan virus infection and its antiviral effect in the hantavirus Syrian hamster model. For this purpose, C57Bl/6 mother mice were treated subcutaneously with daily doses of chloroquine. Subsequently, 1-day-old suckling mice were inoculated intracerebrally with 5 x 102 Hantaan virus genomes. In litters of untreated mothers, none of the pups survived challenge. The highest survival rate (72.7% of pups) was found when mother mice were administered a concentration of 10 mg/kg chloroquine. Survival rates declined in a dose-dependent manner, with 47.6% survival when treated with 5 mg/kg chloroquine, and 4.2% when treated with 1 mg/kg chloroquine. Assessing the antiviral therapeutic and prophylactic effect of chloroquine in the Syrian hamster model was done using 2 different administration routes (intraperitoneally and subcutaneously using an osmotic pump system). A delay in onset of disease was noted and for the osmotic pump, 60 % survival was observed. Our results show that chloroquine can be highly effective against Hantaan virus infection in newborn mice and against Andes virus in Syrian hamsters.